[Behavioral Objectives in English.] - Meade, Richard; Virginia Association of Teachers of English ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This edition of the "Virginia English Bulletin" is devoted primarily to articles about behavioral objectives and the teaching of English. In "Behavioral Objectives for English?" Richard A. Meade argues that these objectives ought to include the acquisition not only of skills and knowledge but also of understandings, insights, and feelings. He also asserts that exact measurement of insights is not possible. Robert W. Reising, in "The Affective Fallacy: More on Behavioral Objectives and the Teaching of English," argues that these objectives do not have to exclude the affective domain and that English teachers should not let others construct their behavioral objectives. In "Backlash or Backwash?" Robert T. Robertson argues that the movement for creating these objectives in English is inherently mechanistic, simplistic, and reactionary, and that it should be resisted by the humanistic teacher. Robert P. Hilldrup, in "Accountability for Achievement in English," argues that English teachers should be accountable for certain objective skills they can transmit, but that their overall objective is teaching communications, an achievement which is difficult to measure. (DI)
Educational level discussed: Elementary Education.
Educational level discussed: Secondary Education.
Virginia English Bulletin, v20 n3 p3-19, 24-27 Winter 1970.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Accountability; Affective Objectives; Behavioral Objectives; Cognitive Objectives; Communication Skills; Elementary Education; English; English Curriculum; School Responsibility; Secondary Education; Student Behavior